Moderate Islam for Harmonization; Analysis and Literature Study in Responding To The Development Of Radicalism - Al Yusuf Ramadhani; Ikhrom Ma`rup; Zaki Alfi Aini Viara; Winarto (Jurnal Al-Hikmah, 2024)
This article discusses the importance of moderate Islam along with the development of radicalism in a number of regions, using a literary approach. The author realizes that terrorism, radicalism, and liberalism are the main topics in this research. Considering that the world is currently known for the problems of radicalism, extremism, and fundamentalism. As an initial illustration based on the topic of news in many media, the issue of radicalism has become a public opinion, especially in the mass media and electronic media. In fact, this act of crime or violence is a phenomenon that we often hear both in the media and in our environmental and social reality. So far, terrorism has been defined as acts of terror, violence, extremism, and intimidation, which often have negative effects on victims. The study "Radicalism, Liberalism, and Terrorism Impacting Islam" explores global events and issues of extremism, fundamentalism, and religious extremism. Several academic questions are presented as the boundaries of the study, including what exactly is the definition of moderate Islam and radicalism, what is the concept of moderate Islam for harmonization? And why is moderate Islam important along with the development of radicalism? Using the literature approach in this article can provide an in-depth description of the condition of human groups, situations, ideological systems, or phenomena today. It can also provide a systematic, honest, and accurate explanation of the events, characteristics, and relationships between the phenomena studied.